-5(4x-2)=-2(6x+3)

Simple and best practice solution for -5(4x-2)=-2(6x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(4x-2)=-2(6x+3) equation:


Simplifying
-5(4x + -2) = -2(6x + 3)

Reorder the terms:
-5(-2 + 4x) = -2(6x + 3)
(-2 * -5 + 4x * -5) = -2(6x + 3)
(10 + -20x) = -2(6x + 3)

Reorder the terms:
10 + -20x = -2(3 + 6x)
10 + -20x = (3 * -2 + 6x * -2)
10 + -20x = (-6 + -12x)

Solving
10 + -20x = -6 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
10 + -20x + 12x = -6 + -12x + 12x

Combine like terms: -20x + 12x = -8x
10 + -8x = -6 + -12x + 12x

Combine like terms: -12x + 12x = 0
10 + -8x = -6 + 0
10 + -8x = -6

Add '-10' to each side of the equation.
10 + -10 + -8x = -6 + -10

Combine like terms: 10 + -10 = 0
0 + -8x = -6 + -10
-8x = -6 + -10

Combine like terms: -6 + -10 = -16
-8x = -16

Divide each side by '-8'.
x = 2

Simplifying
x = 2

See similar equations:

| 2*cos^2x=sinx | | Ln(x-4)=ln(x+6)-lnx | | 2x-3+(4x-10)=180 | | t^2+t+56=0 | | (4t+2)(5t-7)=0 | | 0.5x-0.23=5.77 | | (5y+2)-1=(1-2y) | | -2+11=4y-7y | | x^4-6ax^3+9a^2x^2-1= | | 60+0.50r=1.30r | | 4v=3v-8 | | x+3=6x+2 | | -36.838+10m=-2.3(-5.6m+6.5) | | 2y+72=180 | | (3p-2)(p+9)=0 | | h+9.5=-9.7 | | 25x^3+15x^2+2x=0 | | 3x+2(5x+4)=43 | | 7e^5x+8=0.23 | | 8x^2(2x+9)+(2x+9)=0 | | a/10-8=24 | | 5x+2x-3=17 | | 28-2c=6c+4 | | 12x^2-x=16x+40 | | 2p^2+6p+3=0 | | 180=(6x-19)+(3x+32) | | -4r^2+3+r=0 | | 2w+17=21+3w | | 12n+25=-35 | | 6r+4=5r-8 | | 6x-1=4x+27 | | 2y-16=y-6 |

Equations solver categories